EVALUATING TEACHER-MADE ENGLISH COURSEBOOK FOR EIGHTH GRADE STUDENTS OF A PRIVATE SCHOOL - Muhammad Ilmi Safrizal; Syafi’ul Anam; Ahmad Munir (Mukaddimah: Jurnal Studi Islam, 2024)
This study evaluates an English coursebook developed by an English teacher for 8th-grade students at a private bilingual school in Sidoarjo, Indonesia. To meet the objectives of the integrated curriculum applied by the school, teachers are responsible for facilitating students by providing appropriate coursebooks for teaching and learning activities. This study uses a qualitative content analysis framework to assess the coursebook's alignment with the curriculum, its suitability for students' and teachers' needs, and its overall quality based on Byrd & Schuemann's (2014) evaluation criteria. The findings indicate that the textbook effectively aligns with the curriculum and is well-structured. However, it lacks a strong emphasis on communicative language teaching and opportunities for authentic language use and the development of communicative competence. While the textbook's content and presentation are generally sufficient for the teacher and students, improvements are necessary, including more varied exercises, supplementary materials, and explicit teacher guidance. The findings highlight the need for further development to enhance the textbook's effectiveness in fostering English language proficiency among students. Keyword: Coursebook; Learning material; ELT, Kurikulum Merdeka